The Influence of Product Quality and Price on Online Purchase Interest in the Fashion Category on Lazada: Pengaruh Kualitas Produk dan Harga Terhadap Minat Beli Online Kategori Fashion Di Lazada - Sarereake, Roberta Daniella; Puspa Leni (Perkumpulan Doktor Indonesia Maju, 2024)
The aims of This study is to examine the effect of product quality and price on online buying intention in the fashion category at Lazada among consumers in the South Siberut sub-district. This study used quantitative methods with an associative design. The population in this study were people in South Siberut sub-district who had never made an online purchase at Lazada. The number of samples in this study were 96 respondent. The data analysis technique used is multiple linear regressiom analysis, t-test and f-test are the hypothesis testing. The results of this study show that partially product quality and price has positive and significant effect on online buying interest in the fashion category at Lazada. Based on the F test, product quality and price simultaneously have positive and significant effect on online buying intention in the fashion category at Lazada among consumers in the South Siberut sub-district. R square is 0.269. This means that product quality and price are able to influence online buying intention in the fashion category at Lazada for consumers in South Siberut sub-district with a percentage of 26.9% while the remaining 73.1% is influenced by other variable not examined in this study such as promotion and service quality. Thus, it can be concluded that if you want to improve online buying intention in fashion categories at Lazada for consumers in South Siberut sub-district, product quality and price need to be considered by seller of fashion category at Lazada